Improving the MSME Capability of the Madurese Community Through Mobile Series Applications and Digital Marketing Training - Amaliyah, Amaliyah; Dimisyqiani, Erindah; Apriliani, Lydia; Sedianingsih, Sedianingsih (UKInstitute, 2022)
Technology is one of the keys to the success of SMEs. However, this is not the case in areas with limited knowledge and special skills in operating technology. Creativity and innovation in batik in Madura grew significantly along with assistance from the local government. With adequate production potential and sufficient capital, batik sales must increase. It cannot increase the poverty level in Candi Burung Village, Pamekasan Regency. Welfare improvement has not occurred due to a lack of knowledge about how to develop product innovation and does not have the skills to promote the work to the fullest. Therefore, this service aims to introduce e-commerce and social media applications, product innovation training, and develop a mobile series application system that can make it easier for batik artisans to support batik works. The methods that will be used are: creating an andragogy training application that maximizes the participation of artisans to think critically and have a dialogue by organizing socialization on the use of applications and developing promotions through digital marketing platforms. This service is carried out with the hope that it can advance the knowledge and skills as well as the ability of artisans to carry out the process of distributing their work which in turn can improve the welfare of the artisans.